Phenolic Compounds and Antioxidant Activity of Cocoa and Chocolate Products - Ibrić, Amerisa; Ćavar, Sanja (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Cocoa is the fruit of the tree Theobroma cacao L., growing in tropical regions of Africa and South America. Prefermented and fried cocoa serves as a basic raw material for the preparation of chocolate food products. Cocoa is extremely rich in antioxidants, which are responsible for the overall health of the humans. These antioxidants include polyphenols and catechins. This paper presents the investigation of total phenolic contents and antioxidant activity of extracts obtained from cocoa powder and different types of chocolate. The total content of phenolic compounds was determined by spectrophotometric Folin-Ciocalteu method and it varied from 0.046 ± 0.013 to 0.376 ± 0.022 mg GAE/g. The antioxidant activity of the extracts was tested using total antioxidant capacity method. The IC50 value was in the range of 1.968 ± 0.076 mg/ml to 42.200 ± 1.737 mg/ml. Cocoa powder and chocolate with a high content of cocoa contain relatively high amount of total phenolics, as well as high antioxidant capacity.